2019
DOI: 10.25259/sni_528_2019
|View full text |Cite
|
Sign up to set email alerts
|

Acute presentation of spinal gouty arthritis: A case report and review of literature

Abstract: Background:Gout is an inflammatory arthritis that results from faulty purine metabolism, affecting approximately 4% of adults in the US, and predominately affects people in the fourth decade of life. Further, spinal gout is rarely the first presentation of gout, especially in younger individuals.Case Description:A 26-year-old male came to the emergency room with acute lower extremity numbness and weakness. The MR demonstrated an enhancing epidural lesion at T6–T8 in the mid-thoracic spine. He subsequently unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The authors noted a white, cheese-like material causing dural compression that was confirmed to have negatively birefringent crystals on analysis. 49 Overall, gout with spine involvement should be considered in patients with a known history of gout and back pain that does not respond to conservative management. Diagnosis can be made with imaging via DECT and/or biopsy.…”
Section: Spinementioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted a white, cheese-like material causing dural compression that was confirmed to have negatively birefringent crystals on analysis. 49 Overall, gout with spine involvement should be considered in patients with a known history of gout and back pain that does not respond to conservative management. Diagnosis can be made with imaging via DECT and/or biopsy.…”
Section: Spinementioning
confidence: 99%
“…The authors noted a white, cheese-like material causing dural compression that was confirmed to have negatively birefringent crystals on analysis. 49…”
Section: Spinementioning
confidence: 99%